Pectin-Zein-IPA nanoparticles promote functional recovery and alleviate neuroinflammation after spinal cord injury - Xianghang Chen; Beini Wang; Abdullah Al Mamun; Kaiyi Du; Shengfu Wang; Qianqian Hu; Xinyuan Chen; Yang Lu; Anyu Du; Yueqi Wu; Jiaqin Shao; Shuangshuang Wang; et al. (Journal of Nanobiotechnology)
Abstract Introduction Spinal cord injury (SCI) impairs the balance of gut microbiomes, which further aggravates inflammation in the injured areas and inhibits axonal regeneration. The intestinal microbiome plays an important role in SCI and regulating intestinal microbiome promotes SCI repair. However, current studies have shown that indole-3 propionate (IPA), a metabolite of gut bacteria, can promote axonal regeneration. However, the short half-life of IPA limits its effectiveness. Gut microbiota plays a role in the progression of SCI, but the studies about diet regulates intestinal flora metabolites to improve SCI are still limited and lack guiding significance. Results The results showed that Pectin-Zein-IPA NPs treatment improves motor function recovery, inhibits the activation of oxidative stress, enhances axonal regeneration and activates AKT/Nrf-2 signaling pathway following SCI. Further analysis showed that Pec-Zein-IPA NPs treatment reduced the intestinal flora metabolite accumulation of L-methionine, and alleviated neuroinflammation by improving autophagy and inhibiting pyroptosis. Pec-Zein-IPA may reduced neuroinflammation after SCI by decreasing the abundance of Clostridia − UCG-014, Clostridia − vadinBB60 − group, Shewanella (positively correlated with L-Methionine) and increasing the abundance of Parasutterella (negatively correlated with L-Methionine). Conclusions Our findings provide a strategy for oral drug research in SCI. The results suggest that Pectin-Zein-IPA NPs have potential advantages for treatment and management of SCI. Reducing L-methionine intake may help reduce neuroinflammation after SCI. Graphical Abstract